PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN PT. BANK SYARIAH X MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Ayu Wardani, Rizky Aprilia (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract – performance is a record of the outcome of the function of a particular job or activity of an employee for a certain period of time (Gomes, 2000). This study aims to examine the effect of compensation financial and compensation non financial on performance of employee with motivation as intervening variabel involving 35 people as respondent with using partial least square (PLS) analysis method and sobel tests to test the mediating effect. Data were obtained through observation and questionnaire distribution.This study shows two point, first compensation financial has a significant positive effect on work motivation and work motivation has a significant positive effect on employee’s performance. Indirect influence between compensation financial on performance of employee through work motivation that is partial of mediation due to the effect between compensation financial variable on performance also significant. Second, compensation non financial has a significant positive effect on work motivation. Indirect influence between compensation non financial on performance through work motivation that is full of mediation due to the effect between compensation non financial variable on performance of employee not significant. Keywords: compensation financial, compensation non financial, work motivation, and performance of employee